If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -6x = -1x + -1 + 16 Reorder the terms: 15 + -6x = -1 + 16 + -1x Combine like terms: -1 + 16 = 15 15 + -6x = 15 + -1x Add '-15' to each side of the equation. 15 + -15 + -6x = 15 + -15 + -1x Combine like terms: 15 + -15 = 0 0 + -6x = 15 + -15 + -1x -6x = 15 + -15 + -1x Combine like terms: 15 + -15 = 0 -6x = 0 + -1x -6x = -1x Solving -6x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -6x + x = -1x + x Combine like terms: -6x + x = -5x -5x = -1x + x Combine like terms: -1x + x = 0 -5x = 0 Divide each side by '-5'. x = 0 Simplifying x = 0
| 7+10z-6=8z+19-4z | | 3x+6=-5x-42 | | a*4+63=a*7-9 | | 3y-22=y+14 | | -3(2x+1)=8 | | y+14=2y+2 | | -7(v+4)+3v+6=8v+11 | | 80-4x=14x+20 | | 2y+2=3y-22 | | 5x+-2*(x+6)+2=4*(x-2)+13 | | 4x-y=2z | | 4n-2=10n+46 | | (-11x^2+1x+1)-(-11x^2-22x)= | | 4x-2(x+2)=2(2x-2)-2(x-3) | | 4+12x=26+x | | 4(-3.4-7.4x)=116.64 | | (2x+1)=(x+3) | | 6-3(2x+1)=8-4x | | 7x+3y+5z-4x+2z-4= | | 12x-1=3x+14 | | 1/4(x+1)=9 | | X(0)+3y=-5 | | 14sin^2=7 | | (2x-3)4x=0 | | -2x^2+9x-12=0 | | 3x+5x+3x-13x=-7+3 | | -3x+6(5x+3)=-2 | | 12x=2y+3 | | 10b-15=-115 | | 1+2=2+a | | 5(t-3)=35 | | Y(y+4)-y(y-3)-9y= |